(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Artificial intelligence opens new opportunities for adding value to industry, transport, and society. New technologies are everywhere and are becoming increasingly established in many aspects of life. AI applications are endless to discuss, develop, and deploy. This study looks at the most used applications of artificial intelligence in transport. On the other hand, cybersecurity is also a growing technical and technological concept. Many companies engaged in the development of technical and technological solutions with applications in transport have incorporated information technology into their business. This requires companies and organizations to implement more security measures. The need to protect data and information increases the requirements for cybersecurity, and it is also believed that artificial intelligence substantially impacts cybersecurity. Machine learning is already heavily induced in the latest technologies supporting cybersecurity. The article reviews the literature and explores the overall impact of artificial intelligence on cybersecurity.